Lightweight refractory based on silicon carbide dust and method for its production
By treating silicon carbide dust through a cascaded impurity removal and segmented sintering process, a lightweight refractory material with high SiC content and low impurities is prepared, solving the problem of resource utilization of silicon carbide dust. This process achieves efficient foaming and improved refractory performance, making it suitable for industrial kiln insulation layers and building insulation.
Patent Information
- Application Number
- CN202611262049.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-03
AI Technical Summary
In existing lightweight refractory material technologies, silicon carbide dust has a low resource utilization rate, resulting in resource waste and environmental hazards. Furthermore, existing processes cannot effectively utilize the SiC aggregate and alkali-activated SiO2 components in the dust, leading to instability in the foaming process and affecting refractory performance.
A series of impurity removal processes, including water washing, acid washing, and alkali washing, are used to treat silicon carbide dust. Combined with mechanical ball milling and segmented sintering processes, a highly reactive system is formed. Lightweight refractory materials are prepared through foaming with modified additives and synergistic foaming with ammonia gas generated from the hydrolysis of AlN in aluminum ash.
It significantly improves the SiC content and purity of silicon carbide dust, reduces the impact of impurities, and forms a lightweight refractory material with narrow pore size distribution and high closed-pore rate, reducing the risk of cracking. It has excellent environmental and economic benefits and is suitable for industrial kiln insulation layers and building insulation.
Smart Images

Figure CN123026451A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lightweight refractory materials technology, specifically to a lightweight refractory material based on silicon carbide dust and its preparation method. Background Technology
[0002] Silicon carbide (SiC) is an important abrasive and refractory raw material. During its production, lumps are ground using equipment such as Raymond mills and air jet mills. The resulting fine powder (commonly known as "collection dust"), collected by a cyclone dust collection system, has a fineness of ≤5μm and accounts for approximately 5-10% of the finished product. This type of collection dust contains 5-10 percentage points less SiC than the finished product and includes free carbon, unreacted SiO2, elemental silicon, and impurities such as iron, aluminum, and calcium oxides. Currently, most companies simply stockpile or landfill this collection dust, which not only wastes valuable SiC resources but also poses a potential environmental hazard due to the ultrafine dust.
[0003] Existing lightweight refractory materials mainly use high-purity alumina, silicon dioxide, and silicon carbide as raw materials, which are obtained by adding pore-forming agents or foaming agents and sintering at high temperatures. For example, silicon carbide particles are used as aggregates, and clay or cement binders are added to form a porous structure using the combustible material burn-off method or foaming method. These technologies have the following shortcomings: high raw material costs, heavily relying on natural or synthetic powders; the foaming process has stringent requirements on the matching of slurry rheology and curing time, resulting in a narrow process window; and the simultaneous utilization of SiC aggregate and alkali-activated SiO2 components in silicon carbide dust has not been effectively achieved, making it impossible to realize the high-value co-utilization of solid waste. At the same time, the resource utilization rate of silicon carbide dust in existing technologies is low, resulting in high environmental pressure. Most purification processes only use single acid washing to treat the dust, which has limited effect on the removal of free silicon, elemental silicon, and encapsulated metal oxides. Residual free silicon will react prematurely in the subsequent alkali activation process, disrupting the foaming-curing balance, while metallic impurities will affect the high-temperature refractory performance.
[0004] Therefore, there is an urgent market and environmental demand for developing a lightweight refractory material preparation technology that uses silicon carbide dust as the main raw material and integrates impurity removal, alkali-activated foaming, and sintering. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a lightweight refractory material based on silicon carbide dust and its preparation method.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing a lightweight refractory material based on silicon carbide dust, comprising the following preparation steps: S1. Preparation of modified silicon carbide dust collector ash: S11. By weight, mix 90-100 parts of silicon carbide dust with 300-500 parts of deionized water, stir and wash at 300-400 rpm for 15-30 minutes, let stand and filter to obtain pretreated silicon carbide dust. S12. Add the pretreated silicon carbide dust to 200-500 parts of modified mixed acid, and stir at 200-300 rpm at 50-80℃ for 1-4 hours. After filtration, wash the filter cake 2-3 times with deionized water, and then add it to 200-400 parts of 0.5-2 mol / L sodium hydroxide solution. Stir at 200-300 rpm at 60-80℃ for 0.5-2 hours. The modified mixed acid is prepared by mixing hydrochloric acid, nitric acid, hydrofluoric acid and citric acid in deionized water. S13. Filter the material obtained in step S12. Wash the filter cake repeatedly with deionized water until the washing liquid is neutral. Then dry the filter cake at 100-105℃ to constant weight. After removing it, you will get modified silicon carbide dust. S2. Add the modified silicon carbide dust obtained in step S1, 20-50 parts of aluminum ash, and 90-100 parts of the modified precursor into a planetary ball mill and ball mill for 20-60 minutes. After passing through an 80-200 mesh sieve, the modified powder is obtained. The modified precursor is prepared by mixing fly ash, metakaolin, slag powder, silica fume, sodium silicate, and sodium metasilicate. S3. Add 15-20 parts of modifying agent and 80-120 parts of deionized water to the modified powder obtained in step S2, stir at 300-800 rpm for 4-10 min, pour into a mold, and let stand at 40-80℃ for 12-48 h to obtain a lightweight foamed preform; the modifying agent is prepared by mixing polyacrylamide, hydrogen peroxide, sodium dodecyl sulfate, borax, sodium gluconate and triethanolamine in deionized water; S4. The lightweight foamed preform obtained in step S3 is subjected to first-stage sintering, second-stage sintering and third-stage sintering in sequence. After cooling to 780-800℃ at a cooling rate of 1-3℃ / min, it is cooled to room temperature with the furnace to finally obtain a lightweight refractory material based on silicon carbide dust.
[0007] Preferably, in step S12, the preparation of the modified mixed acid includes the following steps: S121. By mass, slowly add 150-250 parts of 6 mol / L hydrochloric acid solution and 40-80 parts of 68% nitric acid solution to 150-200 parts of deionized water while stirring at 200-300 rpm. S122. Slowly add 5-15 parts of hydrofluoric acid with a mass concentration of 40% and 2-8 parts of citric acid to the mixture obtained in step S121, and stir at a speed of 200-250 rpm until completely dissolved to obtain modified mixed acid.
[0008] Preferably, in step S2, the preparation of the modified precursor includes the following steps: S21. By weight, add 40-70 parts fly ash, 10-30 parts metakaolin, 5-20 parts slag powder, and 3-10 parts silica fume into a high-speed mixer and stir until uniformly mixed to obtain a preliminary mixture. S22. Add 5-15 parts of sodium silicate and 5-12 parts of sodium metasilicate to the preliminary mixture obtained in step S21, stir and mix at 300-500 rpm for 15-30 minutes, and then pass through a 100-mesh sieve to obtain the modified precursor.
[0009] Preferably, in step S2, the ball-to-material ratio of the planetary ball mill is 2-5:1, and the rotation speed is 200-400 rpm.
[0010] Preferably, in step S3, the preparation of the modified additive includes the following steps: S31. By weight, add 0.1-0.2 parts of polyacrylamide to 10-15 parts of deionized water and stir slowly until completely dissolved to obtain a PAM solution; S32. Mix 8-15 parts of 30% hydrogen peroxide solution, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of borax and 1-3 parts of sodium gluconate, and stir until completely dissolved; S33. Add the PAM solution obtained in step S31 and 0.5-2 parts of triethanolamine to the solution obtained in step S32, and stir at 300-400 rpm for 3-5 minutes to obtain the modified additive.
[0011] Preferably, in step S4, the heating rate of the first stage sintering is 0.5-1.5℃ / min, the final temperature is 150-200℃, and the holding time at the final temperature is 1-3h. The first stage sintering is a preheating and dehumidification section, which allows the free water and interlayer water of the geopolymer gel in the green body to evaporate slowly, avoiding cracking of the green body due to rapid water vapor escape.
[0012] Preferably, in step S4, the heating rate of the second-stage sintering is 1-2℃ / min, the final temperature is 500-700℃, and the holding time at the final temperature is 0.5-1h. The second-stage sintering is a medium-temperature transition section, during which the geopolymer matrix undergoes dehydroxylation and initial densification, while the alkali metal oxides begin to volatilize. By slowly heating and holding the temperature in between, the alkali metal oxide vapors gradually escape without causing localized severe gas expansion or pore wall damage.
[0013] Preferably, in step S4, the heating rate of the third-stage sintering is 2-5℃ / min, the final temperature is 900-1300℃, and the holding time at the final temperature is 1-4h. The third-stage sintering is a high-temperature sintering section. The sintering atmosphere can be selected as needed: air to promote partial oxidation of SiC for secondary pore formation, or nitrogen to suppress excessive oxidation and retain more SiC aggregate strength. During sintering, the geopolymer matrix transforms into a ceramic phase, and the residual SiC is partially oxidized to generate SiO2 gas, forming secondary pores.
[0014] Secondly, the present invention provides a lightweight refractory material based on silicon carbide dust, which is prepared by the above-mentioned method for preparing lightweight refractory materials based on silicon carbide dust.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention processes silicon carbide dust through a series of steps including water washing, acid washing, and alkali washing to remove soluble salts, metal oxides, and free silicon. The resulting modified silicon carbide dust has a SiC content of up to 94.25%, which can be used as the main aggregate of the lightweight refractory material of this invention. The modified mixed acid used in the acid washing effectively increases the SiC content of the silicon carbide dust and avoids the negative impact of impurities on the foaming process and refractory performance. Mechanical ball milling is used to finely mix modified silicon carbide dust, aluminum ash, and modified precursors, ensuring microscopic uniformity of each component and avoiding localized alkali enrichment. The resulting modified powder and modifiers form a highly reactive system. The ammonia gas generated from the hydrolysis of AlN in the aluminum ash, in conjunction with hydrogen peroxide chemical foaming, significantly improves the formation rate and uniformity of the geopolymer gel during alkali-activated foaming, effectively suppressing bubble coalescence and escape. This results in a lightweight green body with narrow pore size distribution and high closed-cell ratio, facilitating better three-stage sintering. The segmented sintering process allows for the slow removal of bound water, preventing sudden water vapor release and cracking while controlling the uniform volatilization of Na2O, avoiding localized gas expansion and pore wall collapse. Compared to conventional sintering, this invention significantly reduces the cracking risk of large-size products.
[0016] 2. The lightweight refractory material prepared by this invention has a bulk density of 0.58-0.62 g / cm³. 3 It has a compressive strength of 5.3-5.8 MPa, a thermal conductivity of 0.19-0.21 W / (m·K), and a refractoriness of 1280-1290℃. It can be used in industrial kiln insulation layers, building insulation, and pipe cladding. Furthermore, this invention has low cost, requires no expensive additives in the process, allows for the recycling of acid solutions, and enables the resource utilization of alkaline washing solutions, resulting in outstanding overall economic efficiency and significant environmental and social benefits. Attached Figure Description
[0017] Figure 1 This is a process flow diagram for preparing the lightweight refractory material based on silicon carbide dust of the present invention; Figure 2 This is a flowchart illustrating the preparation process of the modified precursor in this invention. Figure 3 This is a process flow diagram for preparing the modified additives in this invention; Figure 4 This is a flow chart of the preparation process of the modified mixed acid in this invention; Figure 5 The X-ray diffraction patterns of silicon carbide dust, modified silicon carbide dust, and lightweight refractory material in Example 1 of the present invention are shown below. Figure 6 This is an optical micrograph of the fracture surface of a lightweight refractory material based on silicon carbide dust obtained in Example 1 of the present invention. Detailed Implementation
[0018] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0019] Example 1 Please see Figure 1-4 This embodiment provides a method for preparing a lightweight refractory material based on silicon carbide dust. Before preparing the lightweight refractory material based on silicon carbide dust, modified mixed acid, modified precursor and modified additive are prepared first.
[0020] Specifically, the preparation steps of the modified mixed acid are as follows: S121. Slowly add 150g of 6mol / L hydrochloric acid solution and 40g of 68% nitric acid solution to 150g of deionized water while stirring at 200rpm. S122. Slowly add 5g of hydrofluoric acid with a mass concentration of 40% and 2g of citric acid to the mixture obtained in step S121, and stir at 200 rpm until completely dissolved to obtain modified mixed acid.
[0021] Specifically, the preparation steps of the modified precursor are as follows: S21. Add 40g fly ash, 10g metakaolin, 5g slag powder and 3g silica fume into a high-speed mixer and stir until evenly mixed to obtain a preliminary mixture; S22. Add 5g of sodium silicate and 5g of sodium metasilicate to the preliminary mixture obtained in step S21, stir and mix at 300rpm for 15min, and then pass through a 100-mesh sieve to obtain the modified precursor.
[0022] Specifically, the preparation steps of the modified additive are as follows: S31. Add 0.1g of polyacrylamide to 10g of deionized water and stir slowly until completely dissolved to obtain a PAM solution; S32. Mix 8g of 30% hydrogen peroxide solution, 1g of sodium dodecyl sulfate, 1g of borax and 1g of sodium gluconate, and stir until completely dissolved; S33. Add the PAM solution obtained in step S31 and 0.5g of triethanolamine to the solution obtained in step S32, and stir at 300rpm for 3min to obtain the modified additive.
[0023] Specifically, the preparation steps of lightweight refractory materials based on silicon carbide dust are as follows: S1. Preparation of modified silicon carbide dust collector ash: S11. Mix 90g of silicon carbide dust with 300g of deionized water, stir and wash at 300rpm for 15min, let stand and filter to obtain pretreated silicon carbide dust. S12. Add the pretreated silicon carbide dust to 200g of modified mixed acid, stir at 200rpm at 50℃ for 1h, and then add the filtered cake to 200g of 0.5mol / L sodium hydroxide solution and stir at 200rpm at 60℃ for 0.5h. S13. Filter the material obtained in step S12. Wash the filter cake repeatedly with deionized water until the washing liquid is neutral. Then dry the filter cake at 100°C to constant weight. After removing it, you will get modified silicon carbide dust. S2. Add the modified silicon carbide dust, 20g aluminum ash, and 90g modified precursor obtained in step S1 into a planetary ball mill, and ball mill at a ball-to-material ratio of 2:1 and a speed of 200rpm for 20min. After passing through an 80-mesh sieve, the modified powder is obtained. S3. Add 15g of modifier and 80g of deionized water to the modified powder obtained in step S2, stir at 300rpm for 4min, pour into a mold, and let stand at 40℃ for 12h to obtain a lightweight foamed preform. S4. The lightweight foamed preform obtained in step S3 is first sintered at a heating rate of 0.5℃ / min, with an end temperature of 150℃ and a holding time of 1h. Then, it is sintered at a second stage at a heating rate of 1℃ / min, with an end temperature of 500℃ and a holding time of 0.5h. Next, it is sintered at a third stage at a heating rate of 2℃ / min, with an end temperature of 900℃ and a holding time of 1h. Then, it is cooled to 780℃ at a cooling rate of 1℃ / min and then cooled to room temperature in the furnace to finally obtain a lightweight refractory material based on silicon carbide dust.
[0024] Example 2 Preparation of modified mixed acid: S121. Slowly add 250g of 6mol / L hydrochloric acid solution and 80g of 68% nitric acid solution to 200g of deionized water while stirring at 300rpm. S122. Slowly add 15g of hydrofluoric acid with a mass concentration of 40% and 8g of citric acid to the mixture obtained in step S121, and stir at 250rpm until completely dissolved to obtain modified mixed acid.
[0025] Preparation of modified precursors: S21. Add 70g fly ash, 30g metakaolin, 20g slag powder, and 10g silica fume into a high-speed mixer and stir until uniformly mixed to obtain a preliminary mixture; S22. Add 15g of sodium silicate and 12g of sodium metasilicate to the preliminary mixture obtained in step S21, stir and mix at 500rpm for 30min, and then pass through a 100-mesh sieve to obtain the modified precursor.
[0026] Preparation of modifying agents: S31. Add 0.2g of polyacrylamide to 15g of deionized water and stir slowly until completely dissolved to obtain a PAM solution; S32. Mix 15g of 30% hydrogen peroxide solution, 3g of sodium dodecyl sulfate, 3g of borax and 3g of sodium gluconate, and stir until completely dissolved; S33. Add the PAM solution obtained in step S31 and 2g of triethanolamine to the solution obtained in step S32, and stir at 400rpm for 5min to obtain the modified additive.
[0027] S1. Preparation of modified silicon carbide dust collector ash: S11. Mix 100g of silicon carbide dust with 500g of deionized water, stir and wash at 400rpm for 30min, let stand and filter to obtain pretreated silicon carbide dust. S12. Add the pretreated silicon carbide dust to 500g of modified mixed acid, stir at 300rpm at 80℃ for 4h, and then add the filtered cake to 400g of 2mol / L sodium hydroxide solution and stir at 300rpm at 80℃ for 2h. S13. Filter the material obtained in step S12. Wash the filter cake repeatedly with deionized water until the washing liquid is neutral. Then dry the filter cake at 105°C to constant weight. After removing it, you will get modified silicon carbide dust. S2. Add the modified silicon carbide dust, 50g aluminum ash, and 100g modified precursor obtained in step S1 to a planetary ball mill, and ball mill at a ball-to-material ratio of 5:1 and a speed of 400rpm for 60min. After passing through a 200-mesh sieve, the modified powder is obtained. S3. Add 20g of modifier and 120g of deionized water to the modified powder obtained in step S2, stir at 800rpm for 10min, pour into a mold, and let stand at 80℃ for 48h to obtain a lightweight foamed preform. S4. The lightweight foamed preform obtained in step S3 is first sintered at a heating rate of 1.5℃ / min, with an end temperature of 200℃ and a holding time of 3h. Then, a second sintering is performed at a heating rate of 2℃ / min, with an end temperature of 700℃ and a holding time of 1h. A third sintering is then performed at a heating rate of 5℃ / min, with an end temperature of 1300℃ and a holding time of 4h. Finally, the preform is cooled to 800℃ at a cooling rate of 3℃ / min and then cooled to room temperature in the furnace to obtain a lightweight refractory material based on silicon carbide dust.
[0028] Example 3 Preparation of modified mixed acid: S121. Slowly add 200g of 6mol / L hydrochloric acid solution and 50g of 68% nitric acid solution to 160g of deionized water while stirring at 220rpm. S122. Slowly add 8g of hydrofluoric acid with a mass concentration of 40% and 4g of citric acid to the mixture obtained in step S121, and stir at a speed of 220rpm until completely dissolved to obtain modified mixed acid.
[0029] Preparation of modified precursors: S21. Add 50g fly ash, 15g metakaolin, 10g slag powder, and 5g silica fume into a high-speed mixer and stir until uniformly mixed to obtain a preliminary mixture; S22. Add 10g of sodium silicate and 8g of sodium metasilicate to the preliminary mixture obtained in step S21, stir and mix at 400rpm for 20min, and then pass through a 100-mesh sieve to obtain the modified precursor.
[0030] Preparation of modifying agents: S31. Add 0.14g of polyacrylamide to 13g of deionized water and stir slowly until completely dissolved to obtain a PAM solution; S32. Mix 11g of 30% hydrogen peroxide solution, 2g of sodium dodecyl sulfate, 2g of borax and 2g of sodium gluconate, and stir until completely dissolved; S33. Add the PAM solution obtained in step S31 and 1g of triethanolamine to the solution obtained in step S32, and stir at 350rpm for 4min to obtain the modified additive.
[0031] S1. Preparation of modified silicon carbide dust collector ash: S11. Mix 95g of silicon carbide dust with 400g of deionized water, stir and wash at 340rpm for 20min, let stand and filter to obtain pretreated silicon carbide dust. S12. Add the pretreated silicon carbide dust to 300g of modified mixed acid, stir at 250rpm at 60℃ for 2h, and then add the filtered cake to 300g of 1mol / L sodium hydroxide solution and stir at 250rpm at 70℃ for 1h. S13. Filter the material obtained in step S12. Wash the filter cake repeatedly with deionized water until the washing liquid is neutral. Then dry the filter cake at 103°C to constant weight. After removing it, you will get modified silicon carbide dust. S2. Add the modified silicon carbide dust, 30g aluminum ash, and 95g modified precursor obtained in step S1 to a planetary ball mill, and ball mill at a ball-to-material ratio of 3:1 and a speed of 300rpm for 30min. After passing through a 100-mesh sieve, the modified powder is obtained. S3. Add 17g of modifying agent and 100g of deionized water to the modified powder obtained in step S2, stir at 500rpm for 6min, pour into a mold, and let stand at 50℃ for 24h to obtain a lightweight foamed preform. S4. The lightweight foamed preform obtained in step S3 is first sintered at a heating rate of 1℃ / min, with an end temperature of 180℃ and a holding time of 2h. Then, a second sintering is performed at a heating rate of 1.5℃ / min, with an end temperature of 600℃ and a holding time of 0.6h. Then, a third sintering is performed at a heating rate of 3℃ / min, with an end temperature of 1000℃ and a holding time of 2h. Finally, it is cooled to 790℃ at a cooling rate of 2℃ / min and then cooled to room temperature in the furnace to obtain a lightweight refractory material based on silicon carbide dust.
[0032] Comparative Example 1 The only difference between this comparative example and Example 1 is that the modified silicon carbide dust collector is replaced with unmodified ordinary silicon carbide dust collector; the remaining steps are exactly the same in both comparative example 1 and example 1.
[0033] Comparative Example 2 The only difference between this comparative example and Example 1 is that the modified precursor is replaced with fly ash; the other steps are exactly the same as in Comparative Example 2 and Example 1.
[0034] Comparative Example 3 The only difference between this comparative example and Example 1 is that the modified additive is replaced with a foaming agent and retarder mixture with a mass ratio of 1:1. The remaining steps are exactly the same as in Comparative Example 3 and Example 1.
[0035] Performance testing: The present invention conducted a chemical composition analysis on the raw material silicon carbide dust used in step S11 of Example 1 and the final modified silicon carbide dust, and the results are shown in Table 1 below.
[0036] Table 1. Comparison of the composition of silicon carbide dust collector ash and modified silicon carbide dust collector ash.
[0037] Table 1 shows that after a series of impurity removal processes involving water washing, modified mixed acid washing, and alkali washing, the content of each component in silicon carbide dust changed significantly: the silicon carbide (SiC) content increased from 82.61% before washing to 94.25%, indicating a significant improvement in purity; the carbon (C) content decreased from 3.53% to 0.1%, iron oxide (Fe2O3) from 2.28% to 0.41%, calcium oxide (CaO) from 0.88% to 0.10%, magnesium oxide (MgO) from 0.10% to 0.02%, and the total amount of silicon and silicon dioxide (Si+SiO2) decreased from 8.73% to 4.52%. In addition, the sulfur (S) content increased slightly from 0.023% to 0.110%. Overall, the modification treatment of silicon carbide dust effectively removes free carbon, iron, calcium, magnesium, and other impurities from the dust, significantly improving the purity of SiC.
[0038] The present invention performs X-ray diffraction analysis on the raw material silicon carbide dust used in step S11 of Example 1, the obtained modified silicon carbide dust, and the finally obtained lightweight refractory material based on silicon carbide dust. The results are as follows: Figure 5 As shown in the figure, the main phase of silicon carbide dust is SiC, with strong diffraction peaks of free carbon C and Fe2O3, and weak diffraction peaks of free Si and SiO2. After modification, the modified silicon carbide dust still mainly consists of SiC, but the diffraction peak intensities of free carbon C and Fe2O3 are significantly reduced. The SiC content significantly increases to 94.25% wt%, while the contents of impurities such as free Si+SiO2, free C, Fe2O3, CaO, MgO, and S significantly decrease. This indicates that the impurities are effectively removed after a series of impurity removal processes including water washing, modified mixed acid washing, and alkali washing, providing high-purity, low-impurity raw materials for subsequent foaming and molding.
[0039] Appendix Figure 6This is an optical micrograph of the fracture surface of the lightweight refractory material based on silicon carbide dust obtained in Example 1 of the present invention. Due to the foaming reaction of the modifying agent under alkaline conditions, a large number of irregular pore structures are formed inside the material. These pores significantly reduce the bulk density of the material. At the same time, no obvious cracks or agglomeration defects were observed, indicating that the bubbles are uniformly distributed in the matrix during the foaming process, providing good thermal insulation performance and mechanical strength for the lightweight refractory material.
[0040] According to GB / T 2997-2015 "Determination of Bulk Density, Apparent Porosity and True Porosity of Dense Shaped Refractory Products", the bulk density and closed-cell ratio / apparent porosity of the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 were tested. Using an electronic balance (accuracy 0.001g), a vacuum pump, and an oven, the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 were dried to constant weight at 110℃, and the dry weight m1, the suspended weight m2 after vacuum immersion in water, and the wet weight m3 were calculated. The bulk density and apparent porosity were calculated, and the closed-cell ratio was calculated as: total porosity (mercury intrusion porosimetry) - apparent porosity.
[0041] The compressive strength of the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 5072-2008 "Test Method for Compressive Strength of Refractory Materials at Room Temperature". The lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 were processed into 40×40×40mm cubes using a universal testing machine, with a loading speed of 0.5mm / min, and the failure load was recorded.
[0042] The thermal conductivity of the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 was tested according to GB-T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials". The lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 were processed to dimensions of 300×300×30mm using a steady-state heat flow thermal conductivity meter. The hot surface temperature was 300℃, and the cold surface temperature was room temperature. The heat flow was then measured.
[0043] The refractoriness of the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T7322-2017 "Test Method for Refractoriness of Refractory Materials". The lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 and Comparative Examples 1-3 were processed into cones with a height of 30 mm using a high-temperature test furnace. Their softening and deformation temperatures were observed at a heating rate of 5℃ / min, and the highest refractoriness temperature was recorded. The final data are shown in Table 2 below.
[0044] Table 2 Performance Test Data
[0045] As shown in Table 2, the lightweight refractory materials based on silicon carbide dust obtained in Examples 1-3 are superior to the comparative examples in all aspects of performance. This further illustrates that the modified silicon carbide dust, modified precursor, and modified additives work synergistically to form a highly reactive system, significantly improving the formation rate and uniformity of the geopolymer gel during alkali-activated foaming, effectively inhibiting bubble coalescence and escape, resulting in a narrower pore size distribution and a higher closed-cell rate. Combined with the three-stage sintering process, it effectively controls Na2O volatilization and bubble coalescence, significantly reducing the risk of cracking, improving the success rate of large-size product preparation, meeting the requirements for use in industrial kiln insulation layers, building insulation, and other fields, and possessing excellent resource utilization benefits.
[0046] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lightweight refractory material based on silicon carbide dust, characterized in that, The preparation steps include the following: S1. Preparation of modified silicon carbide dust collector ash: S11. By weight, mix 90-100 parts of silicon carbide dust with 300-500 parts of deionized water, stir and wash at 300-400 rpm for 15-30 minutes, let stand and filter to obtain pretreated silicon carbide dust. S12. Add the pretreated silicon carbide dust to 200-500 parts of modified mixed acid, and stir at 200-300 rpm at 50-80℃ for 1-4 hours. After filtration, wash the filter cake 2-3 times with deionized water, and then add it to 200-400 parts of 0.5-2 mol / L sodium hydroxide solution. Stir at 200-300 rpm at 60-80℃ for 0.5-2 hours. The modified mixed acid is prepared by mixing hydrochloric acid, nitric acid, hydrofluoric acid and citric acid in deionized water. S13. Filter the material obtained in step S12. Wash the filter cake repeatedly with deionized water until the washing liquid is neutral. Then dry the filter cake at 100-105℃ to constant weight. After removing it, you will get modified silicon carbide dust. S2. Add the modified silicon carbide dust obtained in step S1, 20-50 parts of aluminum ash, and 90-100 parts of the modified precursor into a planetary ball mill and ball mill for 20-60 minutes. After passing through an 80-200 mesh sieve, the modified powder is obtained. The modified precursor is prepared by mixing fly ash, metakaolin, slag powder, silica fume, sodium silicate, and sodium metasilicate. S3. Add 15-20 parts of modifying agent and 80-120 parts of deionized water to the modified powder obtained in step S2, stir at 300-800 rpm for 4-10 min, pour into a mold, and let stand at 40-80℃ for 12-48 h to obtain a lightweight foamed preform; the modifying agent is prepared by mixing polyacrylamide, hydrogen peroxide, sodium dodecyl sulfate, borax, sodium gluconate and triethanolamine in deionized water; S4. The lightweight foamed preform obtained in step S3 is subjected to first-stage sintering, second-stage sintering and third-stage sintering in sequence. After cooling to 780-800℃ at a cooling rate of 1-3℃ / min, it is cooled to room temperature with the furnace to finally obtain a lightweight refractory material based on silicon carbide dust.
2. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S12, the preparation of the modified mixed acid includes the following steps: S121. By mass, slowly add 150-250 parts of 6 mol / L hydrochloric acid solution and 40-80 parts of 68% nitric acid solution to 150-200 parts of deionized water while stirring at 200-300 rpm. S122. Slowly add 5-15 parts of hydrofluoric acid with a mass concentration of 40% and 2-8 parts of citric acid to the mixture obtained in step S121, and stir at a speed of 200-250 rpm until completely dissolved to obtain modified mixed acid.
3. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S2, the preparation of the modified precursor includes the following steps: S21. By weight, add 40-70 parts fly ash, 10-30 parts metakaolin, 5-20 parts slag powder, and 3-10 parts silica fume into a high-speed mixer and stir until uniformly mixed to obtain a preliminary mixture. S22. Add 5-15 parts of sodium silicate and 5-12 parts of sodium metasilicate to the preliminary mixture obtained in step S21, stir and mix at 300-500 rpm for 15-30 minutes, and then pass through a 100-mesh sieve to obtain the modified precursor.
4. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S2, the ball-to-material ratio of the planetary ball mill is 2-5:1, and the rotation speed is 200-400 rpm.
5. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S3, the preparation of the modified additive includes the following steps: S31. By weight, add 0.1-0.2 parts of polyacrylamide to 10-15 parts of deionized water and stir slowly until completely dissolved to obtain a PAM solution; S32. Mix 8-15 parts of 30% hydrogen peroxide solution, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of borax and 1-3 parts of sodium gluconate, and stir until completely dissolved; S33. Add the PAM solution obtained in step S31 and 0.5-2 parts of triethanolamine to the solution obtained in step S32, and stir at 300-400 rpm for 3-5 minutes to obtain the modified additive.
6. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S4, the heating rate of the first stage sintering is 0.5-1.5℃ / min, the final temperature is 150-200℃, and the holding time at the final temperature is 1-3h. The first stage sintering is a preheating and dehumidification section, which allows the free water and interlayer water of the geopolymer gel in the green body to evaporate slowly, avoiding cracking of the green body due to rapid water vapor escape.
7. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that: In step S4, the heating rate for the second-stage sintering is 1-2℃ / min, the final temperature is 500-700℃, and the holding time at the final temperature is 0.5-1h. The second-stage sintering is a medium-temperature transition phase, during which the geopolymer matrix undergoes dehydroxylation and initial densification, while the alkali metal oxides begin to volatilize. By slowly heating and holding the temperature intermediately, the alkali metal oxide vapors gradually escape without causing severe localized gas expansion or pore wall damage.
8. The method for preparing a lightweight refractory material based on silicon carbide dust according to claim 1, characterized in that, In step S4, the heating rate of the third-stage sintering is 2-5℃ / min, the final temperature is 900-1300℃, and the holding time at the final temperature is 1-4h.
9. A lightweight refractory material based on silicon carbide dust, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.
